Transforming Curatorial Practices: The Role of AI and Blockchain in Shaping an Ethical Art-Science Paradigm for Public Policy - Dartanto, A. Sudjud; Irawanto, Budi; Hujatnika, Agung (IJCAS (International Journal of Creative and Arts Studies), 2024)
The integration of artificial intelligence (AI) and blockchain technology in curatorial practice offers transformative potential for managing, presenting, and distributing both traditional and digital art. This study explores how AI enhances curatorial processes through advanced data analysis and personalized visitor experiences. AI assists curators in organizing collections and recommending artworks tailored to individual preferences, fostering greater engagement with dynamic, customized exhibitions. Blockchain technology, on the other hand, ensures the provenance of decentralized artworks, guaranteeing authenticity and transparency. It addresses issues like counterfeiting, ownership disputes, and secure transactions, while supporting artists through smart contracts that ensure equitable compensation. However, ethical concerns remain. These include biases in AI algorithms, intellectual property challenges in decentralized NFT platforms, and limited digital access for marginalized artists. Academic studies and case analyses underscore these challenges and advocate for collaboration among curators, artists, technologists, and policymakers. This approach seeks to resolve ethical dilemmas, promote inclusivity, and maintain cultural integrity in implementing these technologies. The study emphasizes the need for public policy frameworks to regulate AI and blockchain, ensuring fair compensation and equitable access to their benefits while safeguarding cultural values. By addressing these concerns, these technologies can unlock new possibilities for the art world. Transformasi Praktik Kuratorial: Peran AI dan Blockchain dalam Membentuk Paradigma Seni-Sains yang Etis untuk Kebijakan Publik Abstrak Integrasi kecerdasan buatan (AI) dan teknologi blockchain dalam praktik kuratorial menawarkan potensi transformatif untuk mengelola, menyajikan, dan mendistribusikan seni baik tradisional maupun digital. Studi ini mengeksplorasi bagaimana AI meningkatkan proses kuratorial melalui analisis data yang mutakhir dan pengalaman pengunjung yang dipersonalisasi. AI membantu kurator dalam mengatur koleksi dan merekomendasikan karya seni yang disesuaikan dengan preferensi individu, mendorong keterlibatan yang lebih besar dengan pameran yang dinamis dan disesuaikan. Di sisi lain, teknologi blockchain memastikan asal-usul karya seni yang terdesentralisasi, menjamin keaslian dan transparansi. Teknologi ini mengatasi masalah seperti pemalsuan, sengketa kepemilikan, dan transaksi yang aman, serta mendukung para seniman melalui kontrak pintar yang memastikan kompensasi yang adil. Akan tetapi, masalah etika tetap ada. Ini termasuk bias dalam algoritma AI, tantangan kekayaan intelektual dalam platform NFT yang terdesentralisasi, dan akses digital yang terbatas untuk seniman yang terpinggirkan. Studi akademis dan analisis kasus menggarisbawahi tantangan-tantangan ini dan mengadvokasi kolaborasi di antara kurator, seniman, ahli teknologi, dan pembuat kebijakan. Pendekatan ini berusaha untuk menyelesaikan dilema etika, mempromosikan inklusivitas, dan menjaga integritas budaya dalam mengimplementasikan teknologi ini. Studi ini menekankan perlunya kerangka kerja kebijakan publik untuk mengatur AI dan blockchain, memastikan kompensasi dan akses yang adil terhadap manfaatnya sambil menjaga nilai-nilai budaya. Dengan mengatasi masalah ini, teknologi ini dapat membuka peluang baru bagi dunia seni.